El transporte del pueblo: los mototaxis y la movilidad cotidiana en Lima - Boose, William (2024)
There are hundreds of thousands of mototaxistas in Lima, and they are vital to everyday mobility in much of the city. Meanwhile, many authorities designate them as threats to «progress» and the «formal order». This article proceeds from that tension, seeking to further understanding of the mototaxi economy, everyday mobility, and transport planning in Lima. The article begins by highlighting the ways that mototaxistas help connect the urban fabric and create space. It then critically analyzes authorities’ efforts to strictly govern mototaxistas, as situated within authorities’ broader war against «informality». As a corrective to authorities’ normative perspectives for how people should move through the city, this article argues that instead of characterizing mototaxis and other forms of transit as «informal», we should understand them as forms of popular transit.